(untitled) (American International Journal of Education and Linguistics Research, 2020)
Unlike vowel insertion (epenthesis), consonant insertion is a rare occurrence in languages. It is against this backdrop that this study examines the occurrence of consonant insertion in Ì̩yí̩nnó̩ as claimed by Ibikunle (2008:122). He (Ibikunle 2008:122) claimed that, there is an insertion of voiced bilabial nasal [m] between two nouns while combining them to form new words. This paper shows that, the voiced bilabial nasal [m] found between two nouns in the lect is not the case of consonant insertion but rather, an associative morpheme (a genitive marker) [mὲ] which has lost its vocalic anchor as a result of hiatus resolution across morpheme boundary. Also, our study reveals that, after [mέ] has lost its vocalic anchor, the nasal feature of [m] got transferred to the (oral) V1 of the second noun across morpheme boundary.